Effect of Substituent Groups on the Adsorption Efficiency of Phenols by Activated Carbon Developed by Hydrothermally Treated Phyllanthus Emblica Fruit Stone - Suhas, Suhas (2024)
In this study, the novel activated carbon developed from Phyllanthus emblica fruit stone, through hydrothermal treatment at low pressure and temperature, was utilized for the removal of 4-nitrophenol, 4-chlorophenol, and phenol from water. The activated carbon produced (AC-HTPEFS) showed a well-developed porosity with a surface area of 569 m2 g−1 and a total pore volume of 0.342 cm3 g−1. The adsorption process was explored and efficiently applied regarding the removal of phenols and substituted phenols from wastewater. Thermodynamic analyses indicated that the adsorption process was endothermic and spontaneous. To analyze the equilibrium data, different isotherm models were employed. The Langmuir model applied best, with maximum adsorption capacities of 0.463, 0.434, and 0.387 mmol g−1 at 25 °C for 4-nitrophenol (4-NP), 4-chlorophenol (4-CP), and phenol, respectively, regarding the AC-HTPEFS. The adsorption was mainly an endothermic process, and the results achieved were slightly higher than those obtained with a commercial activated carbon commonly used for this purpose.